2007
DOI: 10.1021/jf070344+
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Comparison of the Influence of Organic and Conventional Crop Management Practices on the Content of Flavonoids in Tomatoes

Abstract: Understanding how environment, crop management, and other factors, particularly soil fertility, influence the composition and quality of food crops is necessary for the production of high-quality nutritious foods. The flavonoid aglycones quercetin and kaempferol were measured in dried tomato samples (Lycopersicon esculentum L. cv. Halley 3155) that had been archived over the period from 1994 to 2004 from the Long-Term Research on Agricultural Systems project (LTRAS) at the University of California-Davis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(204 citation statements)
references
References 24 publications
12
183
1
2
Order By: Relevance
“…The results of content of total flavonoids were different from those obtained by Bortolo et al (2009) andPacheco et al (2011); according to these studies, the variation of water availability did not interfere with the concentration of this phenolic compound for the calendula crop. Mitchell et al (2007) found that the levels of flavonoids in tomato plants increase in the presence of organic fertilization. Borella et al (2011) observed that the content of total flavonoids did not show significant differences for the treatments using chemical fertilization and organic fertilization in calendula.…”
Section: Resultsmentioning
confidence: 99%
“…The results of content of total flavonoids were different from those obtained by Bortolo et al (2009) andPacheco et al (2011); according to these studies, the variation of water availability did not interfere with the concentration of this phenolic compound for the calendula crop. Mitchell et al (2007) found that the levels of flavonoids in tomato plants increase in the presence of organic fertilization. Borella et al (2011) observed that the content of total flavonoids did not show significant differences for the treatments using chemical fertilization and organic fertilization in calendula.…”
Section: Resultsmentioning
confidence: 99%
“…A long-term study (10 years) of tomatoes in organic and conventional plots showed that quercetin, naringenin and kaempferol content was higher in tomatoes from organic plots and the differences increased along with the cultivation year. These differences were ascribed to the lesser amount of available nitrogen [76]. According to Szafirowska and Elkner [77], higher content of soluble phenols and total flavonoids in organic pepper as compared to conventional one was found.…”
Section: Effect Of Managementmentioning
confidence: 96%
“…Among the benefits reported from the adoption of agroecological practices include increased profitability [11,75]; comparable yields and pest controls [76][77][78][79]; improved water use efficiency in horticultural crops [80], as well as crop performance during drought years [78]; improved soil quality and organic matter content [77,78]; improved and more uniform Nitrogen mineralization, increased organic matter content and soil microbial activity in rotations with tomato [81]; improved biodiversity, ecosystem services, and resilience at both the farm and landscape levels [20,36,75,82,83] and as observed in Kiwi fruit orchards [84]; an improved sustainability index as observed with cacao in Mexico [39,85]; improved nutritional profiles, as observed on long-term trials with tomato [75,86,87]; as well as a reduction of pesticide residues in the body [75,86,88,89], including in children [90]. In turn, the greater ecological balance obtained in agroecological systems through crop diversification and increased soil health often results in a greater activity of above-and below-ground beneficial organisms, resulting in enhanced internal biocontrol mechanisms on the farm [76,79].…”
Section: Research Considerationsmentioning
confidence: 99%